Genetic variability of the ABCC2 gene and clinical outcomes in pancreatic cancer patients. (9th January 2019) - Gentiluomo, Manuel; Puchalt García, Paula; Galeotti, Alice Alessandra; Talar-Wojnarowska, Renata; Tjaden, Christine; Tavano, Francesca; Strobel, Oliver; Kupcinskas, Juozas; Neoptolemos, John; Hegyi, Péter; Costello, Eithne; Pezzilli, Raffaele; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) has an extremely poor prognosis, caused by various factors, such as the aggressiveness of the disease, the limited therapeutic options and the lack of early detection and risk markers. The ATP binding cassette subfamily C member 2 (ABCC2) protein plays a critical role in response to various drugs and is differentially expressed in gemcitabine sensitive and resistant cells. Moreover, single nucleotide polymorphisms (SNPs) in the gene have been associated with differential outcomes and prognosis in several tumour types. The aim of this study was to investigate the possible association between SNPs in the ABCC2 gene and overall survival (OS) in PDAC patients. We analysed 12 polymorphisms, including tagging-SNPs covering all the genetic variability of the ABCC2 gene and genotyped them in 1415 PDAC patients collected within the Pancreatic Disease ReseArch (PANDoRA) consortium. We tested the association between ABCC2 SNPs and PDAC OS using Cox proportional hazard models. We analysed PDAC patients dividing them by stage and observed that the minor alleles of three SNPs showed an association with worse OS [rs3740067: hazard ratio (HR) = 3.29, 95% confidence interval (CI) = 1.56–6.97, P = 0.002; rs3740073: HR = 3.11, 95% CI = 1.52–6.38, P = 0.002 and rs717620: HR = 2.90, 95% CI = 1.41–5.95, P = 0.004, respectively] in stage I patients. In patients with more advanced PDAC, we did not observe any statistically significant association. Our results suggest that rs3740067, rs3740073 and rs717620 could be promising prognostic markers in stage I PDAC patients. Abstract : We investigated the possible association between single nucleotide polymorphisms (SNPs) in the ABCC2 gene and overall survival (OS) in pancreatic ductal adenocarcinoma patients and observed that the minor alleles of three SNPs showed an association with worse OS in stage I patients.